Morphological description of skeletal system of the pelvic limb of a specimen of barn owl (Tyto alba) - Morales M., Pamela (2021)
The barn owl (Tyto alba) is protected as it is considered a beneficial species for agrosilvopastoral activities, the maintenance of ecosystems and for human health. The present descriptive study corresponds to an analysis of a barn owl carcass, where the bones of the pelvic, femoral, tibiotarsal, tarsometatarsal and phalangeal regions were studied. It is concluded that the studied specimen has bone structures similar to other birds, mainly raptors; however, the difference in sizes between the iliac crests, the depth of the fossa of the femoral head, the great fusion between the tibiotarsus and the fibula, the hypotarsus formed only by a lateral projection on the tarsometatarsal bone and the great development of the flexor processes of the nail phalanges.